Kyai, pendidikan Islam, dan elit pemerintah: Studi literatur peran kyai dalam lembaga pendidikan Islam dan pemerintahan - Khusnah, Ema Ummiyatul; Fitri, Nur Lailatul; Ulya, Vita Fitriatul (Maliki Interdisciplinary Journal, 2024)
The article explains the role of kyai in islamic education as well as the reigns of the Dutch colonization, Japan, the old order and the new order. On his way, kyai not only contributed to islamic education but was also active in politics. The political strategies used were national politics, greedy politics, and practical politics. The national politics of kyai participated in the struggle for freedom. The heroic politics of kyai have not only played a role in islamic religious education, using boarding schools as a medium of empowerment, morality, and intellectual community. In the meantime, practical politics was used by the kyai as a means to bring about the civil society and advance the nation.